Eccentric Compression Behavior of Coral Aggregate Geopolymer Concrete Columns Reinforced with Stainless-Steel Rebars - Haiwen Xu; Jiasheng Jiang; Chao Yang (Applied Sciences)
Using coral aggregates instead of natural aggregates can save both raw material transportation costs and time in island construction projects. However, coral aggregates are characterized by high brittleness, low strength, and a high chloride content, which result in the brittleness and durability of coral aggregate concrete (CAC). On the other hand, carbon emissions are prominent in the production of Portland cement. A reinforced concrete structure composed of a stainless-steel rebar (SSR), geopolymer concrete, and coral aggregate was employed to address these challenges. Considering that columns are commonly used structural elements, this paper investigates the eccentric compression behavior of stainless-steel rebar-reinforced coral aggregate geopolymer concrete columns (SCGCs) by varying eccentricity (e0 = 70, 140, 210, and 280 mm) and reinforcement ratio (ρs = 0.302%, 0.536%, and 0.838%) values. The failure patterns, load–deformation curves, and crack development of SCGCs were obtained. These results indicate that the failure pattern of SCGCs under eccentric compression is similar to that of conventional reinforced concrete columns. However, SCGCs exhibited a greater lateral deformation. A refined load-bearing capacity prediction model for SCGCs was developed by integrating the constitutive model of coral aggregate geopolymer concrete (CAGC). Furthermore, a crack width prediction model specifically suited for SCGCs was developed, considering the differences in the bond performance between CAGCs and the SSR compared to ordinary concrete and carbon steel and the characteristic of the SSR lacking a yield plateau. The calculations using the refined load-bearing capacity prediction model and the crack width prediction model fit well with the experimental results, indicating that these two models have good application prospects.